Timsko načrtovanje, poučevanje in evalvacija pri interesnih dejavnostih - Slatinšek-Mlakar, Aleksandra (Revija za elementarno izobraževanje, 2009)
Team planning, teaching and teamwork evaluation in extracurricular activities. Recent approaches to school teamwork have become more professional and systematic. Teachers have the opportunity now of attending various continuing professional education seminars and workshops in this field, which provide them with the relevant knowledge needed as well as some experience in teamwork. The teamwork within the current school system has been implemented with particular respect given to lesson planning and teaching that is connected to evaluation. In the present article, teamwork is dealt with in a way that connects al I three fields that have been confirmed by practical examples within extracurricular activities. The case describes an implementation of the concept of interdisciplinary participation among teachers, managing staff, students and experts. It consists of a detailed implementation of goals set in the fields of planning, teaching and evaluation. The participants in our study successfully presented a theatre play, a situation that gives positive feedback and provides an excellent example of successful teamwork. The results of an evaluation questionnaire based on the work they did reveal that the project team participants found the project to be a very successful and pleasant experience; therefore they wish to take part in similar creative activities in the future.